Enhancing Plant Diversity Learning with an Ethnobotany-Based E-Booklet: A Focus on the Pandeglang Community - Ene Nurjanah; Rommel P Laguatan (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to develop an ethnobotany-based e-booklet of the Pandeglang community as a supplementary teaching material on plant diversity material for grade X high school students. Methodology: The method used is development research with the ADDIE model, which in this stage is focused on the analysis stage. The analysis was carried out on the concept of the material through concept maps from high school and Campbell Biology books, basic competencies and indicators, and medicinal plant data obtained through interviews and literature studies. Main Findings: The results of the analysis show that there is a match between the material between high school books and international reference books, especially on Bryophyta, Pterydophyta, and Spermatophyta. In addition, 48 types of medicinal plants were obtained that are commonly used by the Pandeglang community and are relevant to be included in the e-booklet. Novelty/Originality of this study: The novelty of this study lies in the integration of local ethnobotanical knowledge into digital learning media based on e-booklets that are contextual and easily accessible